A review of Australian approaches for monitoring, assessing and reporting estuarine condition: II. State and Territory programs. Issue 66 (December 2016) - Hallett, Chris S.; Valesini, Fiona; Scanes, Peter; Crawford, Christine; Gillanders, Bronwyn M.; Pope, Adam; Udy, James; Fortune, Julia; Townsend, Simon; Barton, Jan; Ye, Qifeng; Ross, D. Jeff; et al.
Highlights: Comprehensive review of programs across Australian States and Territories. A systematic analysis of programs is provided in Appendices. Outputs provide a strong basis for evaluating recent Australian progress. Identifies major strengths, limitations, inconsistencies and gaps in each State. Disparate policies, approaches and techniques are employed among States. Abstract: In contrast to Europe, the USA and South Africa, Australia has no specific, overarching federal legislation to underpin a nationally-coordinated framework for monitoring, assessing and reporting estuarine condition. This has resulted in a complex mosaic of diverse approaches and governance structures, hindering the ability to make inter-State comparisons. In this second part of a comprehensive three-part review, we present a systematic appraisal of current and impending approaches for measuring and reporting estuarine condition in each of Australia's States and Territories. A concise summary is provided in each case, supported by extensive appendices containing detailed accounts of relevant monitoring and reporting programs. We synthesise and evaluate this output at the State/Territory level, highlighting areas of improvement and major gaps.